Bearing the Burden - Implications of Tax Reporting Institutions and Image Concerns on Evasion and Incidence - Kaisa Kotakorpi; Tuomas Nurminen; Topi Miettinen; Satu Metsälampi (Center for Economic Studies and ifo Institute (CESifo), 2022)
We investigate effects of tax reporting institutions on evasion and incidence using an experimental double auction market setting. We find that 28% of the sellers are truthful when only sellers report, but that 88% and 64% of them are truthful under costless and costly third-party reporting by buyers, respectively. Reporting behavior therefore responds to the intensity of deterrence. However, we find that prices do not fully reflect the lower taxes of the evaders. Thus, when only sellers report, tax incidence deviates from the prediction of the standard model, and there is deadweight loss even if tax revenue is low. Pricing, incidence, and reporting patterns in all treatments can be explained by a model of lying costs with image concerns that give rise to a motivation to appear honest.
Keywords: H21; H22; H26; D40; D44; D91; 330; tax evasion; tax incidence; third-party reporting; double auction; social image; experiment